Tree Species Diversity, Distribution and Population Structure of Fraxinus xanthoxyloides in Western Himalayas - Kukreti, Akshit; Thapliyal, Manisha; Kurmanchali, Neelam; Ramola, Gaurav Chand; Singh, Rajat (Indian Forester, 2024)
Population structure, distribution pattern and regeneration status of the species are the prerequisite to devise conservation strategies and decision making for forest management activities of any species. The present study was conducted in West Himalayan Dry Juniper Forest, in Chamoli district, Uttarakhand and Dry Broadleaved and Coniferous Forest, Kinnaur district, Himachal Pradesh, India, to investigate the population structure and regeneration status of Afghan Ash tree species. The results of population status of the Afghan ash in Uttarakhand and Himachal Pradesh indicated the dominance of F. xanthoxyloides. In Uttarakhand, maximum IVI value of F. xanthoxyloides was recorded in Malari (170.26), followed by Jhelum (160.13), whereas in Himachal Pradesh, maximum IVI value 161.50 was recorded in Ribba, while, in Jangi site 128.12 IVI value was recorded. Density and total basal area in all the sites of the Afghan ash ranged from 344.44 individuals ha-1 to 482.22 individuals ha-1 and 18.77 m2 ha-1 to 35.65 m2 ha-1 , respectively. The reverse J-shaped curve was observed in all the CBH classes which signify regeneration at the stand level was good and maximum portion of curve with more than one-half of the individual’s occurrence was found to be higher between the girth classes 10.1-20 cm to 20.1-30 cm and decreased with the increase of girth in all the study stands. Anthropogenic disturbances resulted to be declined in populations of Afghan ash and may lead this species to endangered, rare and threatened categories. Therefore, proper conservation and management initiatives with active involvement of local people are urgent need to protect this keystone plant species in their habitat particularly in cold desert regions of Western Himalayas.